BRCA1/2 testing among young women with breast cancer in Massachusetts, 2010–2013: An observational study using state cancer registry and All‐Payer claims data. (21st March 2022) - Pace, Lydia E.; Ayanian, John Z.; Wolf, Robert E.; Knowlton, Richard; Gershman, Susan T.; Hawkins, Summer Sherburne; Keating, Nancy L.
Abstract: Background: Testing for BRCA1/2 pathogenic variants is recommended for women aged ≤45 years with breast cancer. Some studies have found racial/ethnic and socioeconomic disparities in testing. We linked Massachusetts' All‐Payer Claims Database with Massachusetts Cancer Registry data to assess factors associated with BRCA1/2 testing among young women with breast cancer in Massachusetts, a state with high levels of access to care and equitable insurance coverage of breast cancer gene ( BRCA) testing. Methods: We identified breast cancer diagnoses in the Massachusetts Cancer Registry from 2010 to 2013 and linked registry data with Massachusetts All‐Payer Claims Data from 2010 to 2014 among women aged ≤45 years with private insurance or Medicaid. We used multivariable logistic regression to examine factors associated with BRCA1/2 testing within 6 months of diagnosis. Results: The study population included 2424 women; 80.3% were identified as non‐Hispanic White, 6.4% non‐Hispanic Black, and 6.3% Hispanic. Overall, 54.9% received BRCA1/2 testing within 6 months of breast cancer diagnosis. In adjusted analyses, non‐Hispanic Black women had less than half the odds of testing compared with non‐Hispanic White women (adjusted odds ratio [OR] = 0.45, 95% CI = 0.31, 0.64). Medicaid‐insured women had half the odds of testing compared with privately‐insured women (OR = 0.51, 95% CI = 0.41, 0.63). Living in lower‐income areas was also associated with lower odds of testing. Having an academically‐affiliated oncology clinician was not associated with testing. Conclusion: Socioeconomic and racial/ethnic disparities exist in BRCA1/2 testing among women with breast cancer in Massachusetts, despite equitable insurance coverage of testing. Further research should examine whether disparities have persisted with growing testing awareness and availability over time. Abstract : This study examines BRCA1/2 testing rates among women aged ≤45 years with breast cancer in Massachusetts in 2010–2013 using linkage between the state's cancer registry and All‐Payer Claims Data. Despite insurance coverage and guidelines recommending testing, just over half of privately‐ or Medicaid‐insured women received testing. Odds of testing were lower among Black women and Medicaid‐insured women compared with White and privately‐insured women, respectively, and lower among women living in lower‐income compared with higher‐income areas.